Strategies for Building Accessible and Inclusive Rural Tourism Ecosystems in Cross-Border Regions: The Case of Rural and Border Territory - Teresa Paiva; Teresa Felgueira; Catarina Alves; Adriano Costa (Tourism and Hospitality)
The research contributes to developing and implementing four tourist hubs in Salamanca, León, and Zamora (Spain) territories and the District of Guarda (Portugal). These hubs will act as innovation pivots promoting innovative, sustainable, and inclusive rural tourism and creating specific territorial ecosystems in each region. The main objective is to boost new economic activities and generate employment, especially for priority groups, through smart specialisation and strengthening local economies. The research also focuses on strengthening tourism value chains, making them more competitive and resilient, emphasising accessibility and inclusion. Within a focus group methodology, a SOAR analysis was undertaken. Three stakeholder groups from Portugal and Spain participated in this study: consumers, distributors/marketing professionals (tour operators, tourist offices), and producers (hotels, restaurants, and museums). They participated in collaborative activities within the SOAR framework to understand the needs of tourists, especially those with reduced mobility, and to identify barriers and opportunities for innovation in the sector. The results offer a framework for tourism providers to develop Accessible and Inclusive Rural Tourism Ecosystems by enhancing understanding and improving accessibility for groups with specific needs. It outlines actionable methods for creating inclusive tourism hubs as “innovation pivots,” establishing performance metrics, and fostering stakeholder collaboration to guide evidence-based policies.